New developments and biological insights into the farming of Solea senegalensis reinforcing its aquaculture potential - Sofia Morais; Cláudia Aragão; Elsa Cabrita; Luís E.C. Conceição; Maria Constenla; Benjamín Costas; Jorge Dias; Neil Duncan; Sofia Engrola; Alicia Estevez; Enric Gisbert; Evaristo Mañanós; et al. (Reviews in Aquaculture, 2016)
Senegalese sole was one of the earliest identified candidate species with high potential for aquaculture diversification in the south of Europe. Its culture has been possible, and commercially attempted, for several decades, but intensive production has been slow to take off. This has been explained mostly by serious disease problems, high mortality at weaning, variable growth and poor juvenile quality. However, a strong and sustained research investment that started in the eighties has led to a better understanding of the requirements and particularities of this species. More recently, better management and technical improvements have been introduced, which have led to important progress in productivity and given a new impetus to the cultivation of Senegalese sole. As a result, the last 5 years have marked a probable turning point in the culture of sole towards the development of a knowledge‐driven, competitive and sustainable industry. This review will focus on the main technical improvements and advances in the state of knowledge that have been made in the last decade in areas as diverse as reproductive biology, behaviour, physiology, nutritional requirements, modulation of the immune system in response to environmental parameters and stress, and characterization and mitigation of the main disease threats. It is now clear that Senegalese sole has important particularities that differentiate it from other current and candidate marine aquaculture species, which bring about important challenges, some still unsolved, but also notable opportunities (e.g. a nutritional physiology that is better adapted to dietary vegetable ingredients), as will be discussed here.